2014
DOI: 10.1128/mbio.01064-13
|View full text |Cite
|
Sign up to set email alerts
|

Single Clinical Isolates from Acute Uncomplicated Urinary Tract Infections Are Representative of Dominant In Situ Populations

Abstract: Urinary tract infections (UTIs) are one of the most commonly acquired bacterial infections in humans, and uropathogenic Escherichia coli strains are responsible for over 80% of all cases. The standard method for identification of uropathogens in clinical laboratories is cultivation, primarily using solid growth media under aerobic conditions, coupled with morphological and biochemical tests of typically a single isolate colony. However, these methods detect only culturable microorganisms, and characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 82 publications
3
25
0
Order By: Relevance
“…A recent comparison of 16s sequencing to urine culture in patients with UTI also found that the dominant uropathogen identified by culture was the most abundant organism identified by sequencing. 30 Thus, the clinical relevance of the additional species picked up by 16s rRNA analysis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison of 16s sequencing to urine culture in patients with UTI also found that the dominant uropathogen identified by culture was the most abundant organism identified by sequencing. 30 Thus, the clinical relevance of the additional species picked up by 16s rRNA analysis is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Metaproteomic methods have enabled a deeper characterization of the inflammatory response towards uropathogens in cases of UTI and asymptomatic bacteriuria [5,6]. Several studies have characterized the urinary microbiome by 16S rRNA sequencing to study adults with a cumulative number of 253 subjects investigated across these studies (UTI, n=50; other urinary manifestations, n=154; sexually transmitted diseases, n=20; renal transplant samples, n=60) [4,[7][8][9][10][11][12][13][14][15][16][17][18][19]. However, a complete view of the microbiome, including eukarya and viruses, as well as an unbiased characterization of abundance and the identification of virulence factors as presented in this study can only be achieved by comprehensive metagenome analyses using whole genome shotgun sequencing (WGS).…”
Section: Introductionmentioning
confidence: 99%
“…Nextera XT libraries were prepared manually following the manufacturer's protocol (Illumina). Briefly, samples were normalized to 0.2 ng/μl DNA material per library using a Quant-iT picogreen assay system (Life Technologies) on an AF2200 plate reader (Eppendorf), then fragmented and tagged via16 tagmentation. Amplification was performed by Veriti 96 well PCR (Applied Biosystems) followed by AMPure XP bead cleanup (Beckman Coulter).…”
mentioning
confidence: 99%
“…The 16S rRNA PCR assay was performed using the previously published primers, 803F (5′-TTA GAT ACC 119 CTG GTA GTC -3′) and 1392R (5′-ACG GGC GGT GTG TRC -3′) and PCR cycling conditions (Willner et al, 120 2014). Fusion primers with 454 adaptor sequences were ligated to the 803F and 1392R primers to 121 amplify the V5 and V8 regions of the 16S rRNA gene (Willner et al, 2014). PCR reactions were 122 performed as previously described (Pelzer et al, 2018).…”
Section: Next-generation Sequencing 118mentioning
confidence: 99%